Lexical Cohesion in Jennie’s Interview on The Jennifer Hudson Show - Syahadan, Arman; Handayani, Nurma Dhona (IKIP Siliwangi, 2025)
This study employs a qualitative research approach, specifically discourse analysis, to examine the role of lexical cohesion in spoken discourse, drawing on Halliday and Hasan’s (1976) theory . Using a descriptive research design, the study systematically explores how cohesive devices maintain coherence in an interview with Jennie from Blackpink on The Jennifer Hudson Show. Data were collected through an observational method, where the researcher transcribed the interview and selected key excerpts featuring lexical cohesive devices such as repetition, synonymy, antonymy, hyponymy, and meronymy. The analysis followed the referential identity method, categorizing the cohesive devices based on context and participants' identities, with coding applied to identify patterns in their usage. The study finds that repetition is the most frequently used cohesive device, appearing 21 times, followed by synonymy and antonymy (12 instances each). Hyponymy and meronymy are less frequent but still contribute to the richness of the discourse. The findings highlight the importance of repetition in maintaining discourse coherence, while synonymy and antonymy provide variety and contrast. This research offers a deeper understanding of how lexical cohesion functions in informal, spoken settings, contributing to the overall flow and clarity of conversation.